Nilai Daya Terima dan Kandungan Antioksidan pada Kulit Mochi dengan Substitusi Labu Kuning (Cucurbita Moschata) dan Penambahan Pisang Ambon (Musa Paradisiaca Var. Sapientum. L) sebagai Kudapan untuk Lansia: Acceptance Value and Antioxidant Content of Mochi Skin with Substitution of Pumpkin (Cucurbita Moschata) and Addition of Ambon Banana (Musa Paradisiaca Var. Sapientum. L) as a Snack for the Elderly - Delia Galina Putri; Farapti Farapti (Universitas Airlangga, 2023)
Background: Elderly have a risk of degenerative diseases such as stroke, hypertension, and coronary heart disease. The elderly experience decreased ability to eat due to physiological changes, development of nutrient-dense snacks is needed to overcome this. Mochi is a semi-moist snack that is well-known to the public. Mochi skin with pumpkin substitution and the addition of ambon banana as a snack that sources natural antioxidants (vitamins A, C) is expected to overcome the problem of degenerative diseases. Objective: To determine the acceptability value and nutritional content of mochi skin with pumpkin substitution (Cucurbita Moschata) and the addition of ambon banana (Musa Paradisiaca Var. Sapientum.L). Methods: This study was a pure experimental study with randomized group design, three modified treatments of pumpkin puree substitution with percentages of 30%,40%, and 50%, and the addition of 50 grams of Ambon banana puree in 1 recipe. The acceptance test is done by the hedonic test of preference level by 65 panelists. Results of the preferred formula were then subjected to laboratory tests for the content of vitamins A and C by spectrophotometry. Friedman and Wilcoxon Sign Rank Test does the statistical test. Results: Formula F3 (substitution 50% pumpkin and addition of 50 grams Ambon banana) gave good scores on color (3.12), shape (3.12), aroma (3.34), texture (3.28), taste (3.34) and overall (3.34). The nutritional content of F3/portion (60 grams) based on TKPI is energy 112.42 kcal; protein 1.17 g; carbohydrates 24.38 g; fat 1.28 g; vitamin A 59.99 µg; vitamin C 1.81 mg. Conclusion: Mochi skin with pumpkin substitute and Ambon banana has good acceptability value and increased nutritional content compared to the control formula.